The role of ESG performance in firms' resilience during the COVID-19 pandemic: Evidence from Nordic firms - Habeeb Yahya (Elsevier [Commercial Publisher], 2025)
Firms' corporate social responsibility and environmental sustainability issues have been documented to provide a competitive advantage that enhances financial performance, especially in tightened economic situations. Similarly, studies on countries' economic performance during the COVID-19 pandemic show a significant effect of movement restriction (lockdown) as a spread-containment strategy. This paper analyses the exogenous effect of lockdown on firm performance during the COVID-19 pandemic and the role of firms' sustainability in resilience to the pandemic. This study uses a difference-in-differences analysis on data of publicly listed Nordic firms, showing a positive and significant difference in revenue and profitability for firms listed in lockdown countries compared with those in the country without a lockdown. Further analysis shows that sustainability provides resilience for firms during the COVID-19 pandemic, as firms' environmental and social performances are positively related to revenue, profitability, and valuation. This finding supports the conclusion that customer and investor preferences enhance sustainable firms' performance.